School choice with consent: An experiment - Claudia Cerrone; Yoan Hermstrüwer; Onur Kesten (Max Planck Institute for Research on Collective Goods, 2022)
Public school choice often yields student placements that are neither fair nor efficient. Kesten (2010) proposed an efficiency-adjusted deferred acceptance algorithm (EADAM) that allows students to consent to waive priorities that have no effect on their assignment. In this article, we provide first experimental evidence on the performance of EADAM. We compare EADAM with the deferred acceptance mechanism (DA) and with two variants of EADAM. In the first variant, we vary the default option: students can object - rather than consent - to the priority waiver. In the second variant, the priority waiver is enforced. We find that both efficiency and truth-telling rates are substantially higher under EADAM than under DA, even though EADAM is not strategy-proof. When the priority waiver is enforced, we observe that efficiency further increases, while truth-telling rates decrease relative to the EADAM variants where students can dodge the waiver. Our results challenge the importance of strategy-proofness as a condition of truth-telling and point to a trade-off between efficiency and vulnerability to preference manipulation.
hdl:21.11116/0000-0009-F2B5-9
Keywords: C78; C92; D47; I20; K10; 330; efficiency-adjusted deferred acceptance algorithm; school choice; consent; default rules; law